2022
DOI: 10.2147/ijn.s389194
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Nanocomposite Microsponges for Effective Reconstruction of Critical-Sized Calvarial Defects in Rat Model

Abstract: Micro-sized sponge particulates have attracted extensive attention because of their potential to overcome the intrinsic limitations of conventional monolithic scaffolds in tissue engineering. Bioactive nanocomposite microsponges are regarded as potential bone substitute materials for bone regeneration. Methods: Based on a combination of microfluidic emulsion with further freezing and in situ thawing, chitosan (CS)-hydroxyapatite (HAP) microsponges were prepared and characterized in terms of their morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…At the same time point, the amount of mineralized crystals in nHA/CS@PDA and nHA/CS@PDA-Sr was excess to nHA/CS (Figure H). Wang et al reported that hydroxyapatite/chitosan composite microsponges possess a good mineralization ability . The reason for the better mineralization of the composite microspheres possessing PDA coating may be that the catechol structure of dopamine is a strong coordination bond of metal ions, which is more favorable to the formation of apatite …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time point, the amount of mineralized crystals in nHA/CS@PDA and nHA/CS@PDA-Sr was excess to nHA/CS (Figure H). Wang et al reported that hydroxyapatite/chitosan composite microsponges possess a good mineralization ability . The reason for the better mineralization of the composite microspheres possessing PDA coating may be that the catechol structure of dopamine is a strong coordination bond of metal ions, which is more favorable to the formation of apatite …”
Section: Resultsmentioning
confidence: 99%
“…The cells were incubated in a humidified atmosphere with 5% CO 2 at 37 °C. The fresh culture medium was replaced every 2–3 days . The Cell Counting Kit-8 (CCK-8, Dojindo, Kumamoto, Japan) was used to evaluate the proliferation of HUVECs and BMSCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Критические дефекты, описанные в литерату ре, условно можно разделить на два типа. К перво му типу можно отнести дефекты, не требующие в силу своей стабильности дополнительной ауг ментации, профилактически предотвращающей патологический перелом оперируемой кости (округлые фрезевые дефекты черепа [25,30,31], округлые фрезевые дефекты эпифизов бедренной и большеберцовой костей [28]). Ко второму типу от носятся дефекты, требующие стабилизации ввиду высокого риска переломов костей при обычной на грузке -полные сегментарные дефекты бедрен ной кости, фиксированные штифтом [22], пласти ной [32] или аппаратом наружной фиксации [33].…”
Section: статистический анализunclassified